Development of the Jakarta Hajj Hospital Financial System Based on the Open Group Architecture Framework (TOGAF) Approach - Anis Nur Safarina Zaenudin; Bayu Waspodo (CV. AFDIFAL MAJU BERKAH, 2026)
Financial management is a vital component in supporting hospital operations. Jakarta Hajj Hospital faces challenges in the form of an incompletely integrated financial system, manual processes that are prone to human error, and a lack of clear technological architecture guidelines. This study aims to design an integrated financial information system architecture using The Open Group Architecture Framework (TOGAF). The method used is qualitative with the TOGAF Architecture Development Method (ADM) approach that includes the Preliminary phase to Architecture Change Management. Data collection was carried out through observation, interviews, and literature studies. The results of this study are a blueprint of business architecture, data, applications, and technology that integrates BPJS claims management, financial reporting, and patient transactions. The contribution of this study is the provision of strategic guidelines for digital transformation to improve operational efficiency, transparency, and security of financial data at Jakarta Hajj Hospital.